2021
DOI: 10.1002/oby.23120
|View full text |Cite|
|
Sign up to set email alerts
|

Selection of Antiobesity Medications Based on Phenotypes Enhances Weight Loss: A Pragmatic Trial in an Obesity Clinic

Abstract: Little is known about the predictors of response to obesity interventions. Methods: In 450 participants with obesity, body composition, resting energy expenditure, satiety, satiation, eating behavior, affect, and physical activity were measured by validated studies and questionnaires. These variables were used to classify obesity phenotypes. Subsequently, in a 12-month, pragmatic, real-world trial performed in a weight management center, 312 patients were randomly assigned to phenotype-guided treatment or non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 44 publications
0
101
0
Order By: Relevance
“…GE, gastric emptying; OAS, overall appetite score; VAS, visual analog scale increases ghrelin(42). Moreover, the identification of rapid GE can help to individualize treatment strategies in patients with obesity to achieve better weight-loss outcomes(43). Thus, in 2 pilot studies, we have shown that patients with obesity and rapid GE respond better to GLP-1 analogs, exenatide(24), and liraglutide(21).…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…GE, gastric emptying; OAS, overall appetite score; VAS, visual analog scale increases ghrelin(42). Moreover, the identification of rapid GE can help to individualize treatment strategies in patients with obesity to achieve better weight-loss outcomes(43). Thus, in 2 pilot studies, we have shown that patients with obesity and rapid GE respond better to GLP-1 analogs, exenatide(24), and liraglutide(21).…”
mentioning
confidence: 96%
“…GE, gastric emptying; OAS, overall appetite score; VAS, visual analog scale increases ghrelin(42). Moreover, the identification of rapid GE can help to individualize treatment strategies in patients with obesity to achieve better weight-loss outcomes(43). Thus, in 2 pilot studies, we have shown that patients with obesity and rapid GE respond The calorie intake of the next meal, or expected satiation, is influenced by the nutritional properties of the previous meal, homeostatic food intake signals, and learned behavior about expected satiation potential.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We want to apologize to the readers of our recent article published in Obesity (1) for the error in the information regarding clinical trial registration and the lack of clarity in describing the study design. Both issues are addressed in this corrigendum.…”
mentioning
confidence: 99%